2014
DOI: 10.1177/0961203314534909
|View full text |Cite
|
Sign up to set email alerts
|

The effects of rituximab on the lipid profile of patients with active systemic lupus erythematosus: results from a nationwide cohort in Spain (LESIMAB)

Abstract: Our results suggest that rituximab may improve the long-term lipid profile of patients with SLE refractory to standard treatment, mainly by reducing inflammatory activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…A study by Fernández-Nebro et al . [ 29 ], in systemic lupus erythematosus patients who are resistant to conventional therapy, showed that Rituximab may help improve long-term lipid profile indirectly by lowering the inflammatory activity. Hence, overall results concluded that rituximab caused a higher increase in total serum cholesterol, but may be manageable and more tolerable over the long course of therapy compared to tacrolimus ( P = 0.37, 95% CI: −27.94–10.29).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Fernández-Nebro et al . [ 29 ], in systemic lupus erythematosus patients who are resistant to conventional therapy, showed that Rituximab may help improve long-term lipid profile indirectly by lowering the inflammatory activity. Hence, overall results concluded that rituximab caused a higher increase in total serum cholesterol, but may be manageable and more tolerable over the long course of therapy compared to tacrolimus ( P = 0.37, 95% CI: −27.94–10.29).…”
Section: Discussionmentioning
confidence: 99%
“…SLE is a chronic autoimmune disease associated with dyslipidemia ( 40 ). A previous study reported that prior to treatment with rituximab, 69% of SLE patients had dyslipidemia, among which the major abnormalities were LDL and HDL ( 41 ). Elfving et al.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, peripheral blood was collected from 35 age matched young juvenile systemic lupus erythematosus (JSLE) patients (fulfilling The American College of Rheumatology (ACR) classification criteria for lupus (1997) ( Hochberg, 1997 ) or the Systemic Lupus International Collaborating Clinics (SLICC) criteria (2012) ( Petri et al., 2012 ) and 121 young juvenile idiopathic arthritis (JIA) patients (fulfilling the International League of Associations for Rheumatology criteria ( Petty et al., 2004 )) (puberty Tanner stage 4-5) attending a young adult or adolescent rheumatology clinic at University College London Hospital (UCLH) or Great Ormond Street Hospital (GOSH) respectively ( Table S7 and 8 for demographics and clinical data). Patients on biologic therapy were not included in the cohorts due to their known effects on lipids ( Hoffman et al., 2018 ; Daien et al., 2012 ; Fernandez-Nebro et al., 2014 ). Informed written consent was acquired from all donors under the ethical approval reference: REC11/LO/0330.…”
Section: Methodsmentioning
confidence: 99%